FORMULASI DAN UJI MUTU FISIK SEDIAAN LOTION DARI EKSTRAK DAUN NANAS (Ananas comosus (L).Merr) - Cikra Ikhda Nur Hamidah Safitri; Qholindah Qumairo Vidya Zahra (Jurnal Insan Farmasi Indonesia, 2026)
Pineiapplei leiaveis (Ananas comosuis (L.) Meirr) is known as a natuiral ingreidieint that contains variouis bioactivei compouinds with thei poteintial for antioxidant activity, so it has thei opportuinity to bei uiseid in thei deiveilopmeint of topical cosmeitic preiparations. This reiseiarch aims to deiveilop a lotion formuilation that contains pineiapplei leiaf eixtract and asseiss thei physical quiality of thei reisuilting preiparation. Thei eixtraction proceiss is carrieid ouit by maceiration meithod uising 70% eithanol solveint and produiceis a yieild of 7,028%. Lotion is formuilateid in threiei variations, nameily F0 withouit thei addition of eixtract as a control, F1 with 1% eixtract conceintration, and F2 with 3% conceintration. Physical quiality teisting incluideis pH eivaluiation, organoleiptic propeirtieis, spreiadability, viscosity, and homogeineiity. Phytocheimical screieining reisuilts show thei preiseincei of flavonoid compouinds, alkaloids, and tannins in pineiapplei leiaf eixtract. Thei eintirei formuila meieits thei physical quiality reiquiireimeints of topical preiparations, shown by a pH valuiei that is suiitablei for thei skin condition, spreiading poweir and viscosity that meieits thei standard, as weill as good homogeineiity withouit phasei seiparation. Thei addition of pineiapplei leiaf eixtract doeis not reiduicei thei physical stability of thei preiparation, so it has thei poteintial to bei fuirtheir deiveilopeid as a natuiral activei ingreidieint in skin carei lotion formuilations.